Kendang Beleq : Navigasi Etnopedagogis Untuk Memahami Kultural Dalam Pendidikan - Yasa, I Made Ardika; Suastra, I Wayan; Arnyana, Ida Bagus Putu (Widya Sundaram : Jurnal Pendidikan Seni Dan Budaya, 2024)
This article explores the cultural art of Kendang Beleq as an ethnopedagogical navigation to comprehend cultural aspects in education. The findings of this research are expected to provide information and education to enrich the understanding of Indonesian culture, especially in Lombok Island, by integrating the cultural art of Kendang Beleq into the educational process. A qualitative research method with a case study approach is employed to delve into the impact of Kendang Beleq integration in education. Key informants and research participants include students, teachers, and local community members involved in Kendang Beleq learning. The use of data collection instruments such as in-depth interviews, surveys, and observations ensures data variation and represents different perspectives. Through the case study approach and qualitative method, the research demonstrates positive impacts on the development of students' skills and increased cultural awareness. Empowering the local community through Kendang Beleq involvement is also emphasized. The results of this research provide practical recommendations for further development, offering a significant contribution to understanding the role of Kendang Beleq in opening windows of cultural understanding through ethnopedagogy in education.